Cohabitation, Relationship Stability, Relationship Adjustment, and Children’s Mental Health Over 10 Years - Foran, Heather M.; Mueller, Janina; Schulz, Wolfgang; Hahlweg, Kurt (Frontiers in Psychology, 2022)
Understanding risk factors for relationship dissolution and poor relationship adjustment among couples has been an active area of research in relationship science. One risk factor, nonmarital cohabitation, has shown to predict higher rates of relationship dissolution and relationship instability in some samples, but the associations among German parents with children over time are less clear. In this study, we examined the links between nonmarital cohabitation and 10-year outcomes (relationship dissolution, relationship adjustment over time, and child internalizing and externalizing symptoms) in 220 German families with preschool-aged children at the initial assessment followed into adolescence. Families were assessed 7 times over the 10 years and retention at the 10-year follow-up was over 92%. After accounting for multiple testing, only mother’s report of better initial interparental communication predicted whether parents were likely to stay together over the course of the 10 years. Adolescents of parents who cohabited were at higher risk for externalizing symptoms 10 years later compared to children of married parents. In addition, although there were no differences between cohabiting couples and married couples at the initial assessment in relationship adjustment, cohabiting mothers who stayed with their partner over the 10 years showed significantly greater declines in relationship adjustment over the 10 years compared to married mothers. Findings indicate the need for further research that explores family structure and dynamics over time to inform refinement of prevention programs targeting relationships and children’s mental health.